Entrepreneurial Potential Influence to Intention of Students Based on Gender - Lena Ria Bela; Asri Laksmi Riani; Mintasih Indriayu (Randwick International of Social Science Journal, 2021)
Gender inequality is one of the keys to entrepreneurial activity in general and especially for entrepreneurial intentions in encouraging to set up new businesses. Entrepreneurial intention grows from the presence of entrepreneurial potential, so an entrepreneur needs to have an entrepreneurial intention in itself. It is interesting to study whether the entrepreneurial potential of men is stronger than women so that men have more intentions to set up their new businesses than women?. The study method used is hierarchical multiple regression analysis with a research population of 402 students and the sample to be used is 200 students. Proportional stratified random sampling is a type of probability sampling technique used in this study. Test the validity and reliability using the product-moment correlation formula from Pearson and the formula for calculating Cronbach alpha (α). The results of the analysis show Entrepreneurial potential significantly affects student intention, but gender does not significantly moderate the relationship.